Health research ethics review and needs of institutional ethics committees in Tanzania - Ikingura, J K; Kruger, M; Zeleke, W (Tanzania Journal of Health Research, 2008)
No Abstract. Tanzania Health Research Bulletin Vol. 9 (3) 2007: pp. 154-158